2016
DOI: 10.1016/j.frl.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: Psychological barriers in gold and silver prices

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Different studies concluded that price barriers or at least significant deviations from uniformity also exist in other asset classes such as exchange rates (De Grauwe & Decupere, 1992;Mitchell & Izan, 2006), bonds (Burke, 2001), commodities (Aggarwal & Lucey, 2007;Lucey & O'Connor, 2016) and derivatives (Schwartz, Van Ness, & Van Ness, 2004;Chen & Tai, 2011;Jang, Kim, Kim, Lee, & Shin, 2015;Dowling, Cummins, & Lucey, 2016;Palao & Pardo, 2018). Overall, evidence of price barriers in various asset classes seems to be fairly robust.…”
Section: Previous Findingsmentioning
confidence: 99%
“…Different studies concluded that price barriers or at least significant deviations from uniformity also exist in other asset classes such as exchange rates (De Grauwe & Decupere, 1992;Mitchell & Izan, 2006), bonds (Burke, 2001), commodities (Aggarwal & Lucey, 2007;Lucey & O'Connor, 2016) and derivatives (Schwartz, Van Ness, & Van Ness, 2004;Chen & Tai, 2011;Jang, Kim, Kim, Lee, & Shin, 2015;Dowling, Cummins, & Lucey, 2016;Palao & Pardo, 2018). Overall, evidence of price barriers in various asset classes seems to be fairly robust.…”
Section: Previous Findingsmentioning
confidence: 99%
“…According to the market efficiency hypothesis, numbers should not have a preference for one another, and it is also impossible to have a lucrative strategy. But despite psychological barriers, some numbers will alter the process as soon as they are seen, and a lucrative plan can be developed in this case [12].…”
Section: Clusteringmentioning
confidence: 99%
“…It is worth mentioning at this point that, in their investigation on psychological factors that affect precious metals markets, Lucey and O'Connor (2016) emphasize that 2011 was a year marked with high volatility for both the gold and the silver market. Furthermore, Pan (2018) in his study of bubble periods for precious metals markets, identifies two such periods for the market for silver; that is, the period between January-July 2008 and the period from November 2009 to January 2013.…”
Section: Net Directional and Net Pairwise Dynamic Connectednessmentioning
confidence: 99%